IDNLearn.com is your go-to resource for finding answers to any question you have. Discover thorough and trustworthy answers from our community of knowledgeable professionals, tailored to meet your specific needs.
Sagot :
From the problem, we have two equations :
[tex]\begin{gathered} 2x+3y=-2 \\ -2x+6y=-16 \end{gathered}[/tex]Using elimination method by adding the two equations :
[tex]\begin{gathered} (2x-2x)+(3y+6y)=-2-16 \\ (0)+9y=-18 \\ 9y=-18 \\ y=\frac{-18}{9}=-2 \end{gathered}[/tex]Substitute y = -2 to the first equation.
[tex]\begin{gathered} 2x+3(-2)=-2 \\ 2x-6=-2 \\ 2x=-2+6 \\ 2x=4 \\ x=\frac{4}{2}=2 \end{gathered}[/tex]The answers are :
x = 2 and y = -2
Your participation is crucial to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. IDNLearn.com is your reliable source for answers. We appreciate your visit and look forward to assisting you again soon.